Memanfaatkan Media Bacaan Bahasa Inggris dalam Pembelajaran TK - Nur Asyiyah Harahap (Wahdatul Ulum Institute, 2022)
Reading will very have an in with growth of Ianguage a child. Through child reading will be exposed to various writing ways or model and pattern. For example, stylistic of exchequer of the word weared [by] each;every article type ( reading) will differ the one with other. People storybook will be written by differing from the history fiction book, fantasy storybook is of course is also written with style and usage of exchequer of different word with information book.